Three paths of justice : court proceedings, arbitration, and mediation in England - Andrews, Neil (Barrister) (New York : Springer, 2018)
"This revised second edition takes account of developments in the field of dispute resolution, including mediation and arbitration. The book presents a concise account of the English system of civil litigation, covering court proceedings in England and Wales. It is an original and important study of a system which is the historical root of the US litigation system. The volume offers an ... account of the entire range of dispute resolution techniques."--
Introduction -- Principles and transnational dimensions -- First instance proceedings -- Appeals and finality -- Cost and funding -- Enforcement of court judgments and orders -- Protective relief -- Multi-party litigation -- International commerical arbitration -- Mediation in England -- Mediation : a global survey.
Includes bibliographical references (pages 309-338) and index.
Keywords: Justice, Administration of -- England; Civil procedure -- England; Arbitration and award -- England; Mediation -- England; Arbitration and award; Civil procedure; Justice, Administration of; Mediation; England